Hidden Hindu : Book 3 of the Trilogy - Akshat Gupta; GUPTA (Akshat) (Haryana Penguin Random House India Pvt Ltd, 2023)
Who is Devdhwaja: Nagendra or Om? Parimal and LSD struggle to trust each other while Nagendra is resurrected from the dead, unharmed and more powerful than ever before. Parashurama and Kripacharya are trapped in the collapsed Om$1 (Bs past while Vrishkapi is fighting against certain death, which has already consumed Milarepa. Leaving the mighty Ashwatthama clueless, the other immortals are dismantled from all fronts. Where are the remaining words hidden? Will Nagendra find them all and complete the verse, or will the immortals be able to stop him? Unravel the unexpected mystery of the doomed immortals, running out of time.s
Keywords: Indian Fiction; Book 3; Trilogy